A Review of Climate Change and its Effects in the Western Mountainous Water Basin of Nepal - Bista, Raghu Bir; Dahal, Khet Raj; Gyawali, Ram Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
This study was conducted in the period of January 2014 to December 2015. The main objective of the study was to investigate the impact of climate change in the water basin and its catchment areas. The method was a survey of relevant literatures. Climate change is a big issue not only in developed countries but also in developing countries. The study found that the temperature is rising with 2.00 C on average per annum in western Nepal. This is relatively 3 times higher than lower temperature increase within the country and significantly higher in comparison to global trend of temperature variation. Over the last 36 years (1975-2010) in western Nepal, temperature is rising on an average of 1.2°C per annum. This is twice as compared to the global increment. This indicates more vulnerability of climate change in hills and high hills of Nepal. The average rise of temperature in Nepal is 0.06oC per year. The climate-induced disasters are; drought, severe floods, landslide, etc. They also have negative effects in agriculture in the hills and high hills of Nepal. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 23 Year: 2018